Penerapan Media Gambar dalam Pembelajaran Berbahasa Anak di Taman Kanak Kanak Cinta Ananda Kecamatan Syiah Kuala Banda Aceh - Cut Richa Rizriana; Mhd. Harun; Muhammad Iqbal (JIM Pendididikan Bahasa dan Sastra Indonesia, 2019)
This research entitled "The Application of Image Media in Children's Language Learning in Cinta Ananda Kindergarten in Syiah Kuala Banda Aceh" is aimed to find out how a picture media can influence the children's language ability which is applied in children's language learning in Cinta Ananda Kindergarten Syiah Kuala Banda Aceh. The problem statements is how the application of media images in children's language learning in Cinta Ananda Kindergarten Syiah Kuala Banda Aceh. The method used in this research is descriptive qualitative method. Data collection methods used in this study are the record and note techniques. The results of this study are data in the form of types of image media used by teachers in children's language learning. Based on the results of the analysis, children's language skills in the Cinta Ananda Kindergarten  Syiah Kuala Banda Aceh were improved through un-projected image media such as still images in the form of paintings, series drawing and flash card.